Keterampilan Penyiar dalam Membawakan Program Rotasi Obrolan Seputar Literasi di Radio Republik Indonesia (RRI) Pro 2 Pekanbaru - Yantos; Okta Anggelia (Al-Manar Journal of Economic and Social Studies, 2025)
Competition in the digital world is currently increasing rapidly, which is marked by the many innovations that have emerged. This requires the broadcaster RRI Pro 2 Pekanbaru to innovate as well and implement effective broadcasting strategies in order to continue to attract and retain its listeners. Therefore, this study aims to determine the Broadcaster's Skills in Presenting the Literacy Chat Rotation Program on Radio Republik Indonesia (Rri) Pro 2 Pekanbaru. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the strategies implemented by RRI Pro 2 Pekanbaru broadcasters include thorough preparation, the use of persuasive language, and adjusting the broadcasting style according to the characteristics of the sources and listeners. With Ben G. Henneke's Theory, several important things have been compiled in announcing, , eloqutio to choose appropriate and interesting communication styles and physical styles, memoria to remember important points, and pronuntiation to convey messages with the right intonation and expression. The overall implementation of Ben G. Henneke's Theory in the broadcasting skills of the Rotation Program contributes to the listener's experience in listening to radio programs.